Enhancing Tourism at Temam Waterfall Park through the Establishment of an English-Speaking Market Area and Education for Local Vendors: Meningkatkan Pariwisata di Taman Wisata Air Terjun Temam melalui Pembentukan Area Pasar Berbahasa Inggris dan Edukasi bagi Pedagang Lokal - Agus Triyogo; Hamdan; Parwito; Moh.Hafiz Albaridi; Muhammad Thoriqul Khoir; Adji Prahmana Putra; Noval Miftahul Ihsan; Intan Mutia (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Temam Waterfall Tourism Park in Lubuklinggau, South Sumatra, has great potential as a tourist destination with natural beauty in the form of waterfalls and beautiful vegetation. However, there was a decrease in the number of visitors which had a negative impact on the income of local traders. To overcome this problem, initiatives have been carried out in the form of the establishment of an English-speaking market area and training for local traders. This program aims to improve the communication skills of traders in English, so as to better serve tourists and create a more satisfying tourist experience. The training includes communication skills, customer service, and more effective promotional strategies. In addition, this program also encourages environmental care and promotion of local crafts to increase tourist attractions. Activities are carried out through socialization, scheduled training, hands-on practice, and the application of technology to support continuous learning. Periodic mentoring and evaluation are carried out to ensure that the skills acquired are applied in daily practice. The results of this program show that the improvement of traders' communication skills has increased, they are able to serve sellers with simple English. Thus, after the traders can communicate in English, it is hoped that they can bring tourists to return for vacation at the Teem Waterfall Tourism Park.